O22.7 Home-Based Sample Collection Increases Chlamydia Retesting and Detects Additional Repeat Positive Tests: A Randomised Controlled Trial in Three Risk Groups. (13th July 2013) - Smith, K S; Hocking, J S; Wand, H; Chen, M; Fairley, C K; Bradshaw, C S; Read, P; McNulty, A; Saville, M; Tabrizi, S N
Abstract : Background: Chlamydia retesting at three months after treatment is recommended to detect reinfections, but retesting rates are low. We assessed the impact of combining home-collection with SMS reminders on retesting rates in three risk groups. Methods: A randomised controlled trial was undertaken, involving 600 participants diagnosed with chlamydia: 200 men who have sex with men (MSM), 200 women and 200 heterosexual men. Participants were recruited from two Australian sexual health clinics and randomised to the home group (3-month SMS reminder and home-collection) or the clinic group (SMS reminder). The mailed home-collection kit included a self-collected vaginal swab (women), UriSWAB (Copan) for urine collection (heterosexual men), and UriSWAB plus rectal swab (MSM). The primary outcome was the proportion retested at 1–4 months after chlamydia diagnosis, and the secondary outcome was the proportion with repeat positive results at the 1–4 month retest. Any testing outside the study sites was collected and included in the outcomes. An intention to treat analysis was conducted. Results: Overall 61% (183/300) of home group participants retested within 1–4 months of chlamydia diagnosis compared with 39% (118/300) in the clinic group (p < 0.001). According to risk group, the differences were: 62% vs 45% (MSM); 65% vs 38% (women); and 55% vs 34% (heterosexual men); all p < 0.05. Overall the proportion with a repeat positive result at the 1–4 month re-test was 16% (95% CI: 11–23) (30/183) in the home group compared with 10% (95% CI: 5–17) (12/118) in the clinic group: 26% (95% CI: 16–39) vs 11% (95% CI: 4–24) MSM; 12% (95% CI: 5–22) vs 5% (95% CI: 1–18) women; and 11% (95% CI: 4–22) vs 15% (95% CI: 5–31) heterosexual men. Conclusion: SMS reminders combined with home-based collection was a very effective strategy to increase chlamydia retesting in all three risk groups, and also detected additional repeat infections in MSM. The acceptability to patients and health care provider costs are currently being evaluated.